Assessment of Mechanical Properties of Natural Half breed Fibers, Reinforced Polyester Composite Materials - Jeevabharathi , S. (International Journal of Psychosocial Rehabilitation, 2019)
The composite materials are replacing the traditional materials, because of its superior properties such as high tensile strength, low thermal expansion, high strength to weight ratio. The developments of new materials are on the anvil and are growing day by day. In this work the effect of glass fibre hybridization with the randomly oriented natural fibers has been evaluated. the sisal(S),banana(B),E-glass synthetic fibers were chopped and reinforced with polyester matrix. Six layers were prepared in the following stacking sequence of S/B/G,S/G/B,G/S/B,G/S/B/G/S/B/G,S/G/B//S/G/B,B/G/S/B/G/S. The mechanical properties like impact strength, flexural strength and tensile strength were investigated and compared. It was observed that the addition of two and three layer of glass fibre can improve the mechanical properties like tensile. Flexural and impact strength.